A Review of the Literature on the Benefits and Drawbacks of Participatory Action Research - Bennett, Marlyn (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2004)
This paper reviews Participatory Action Research as a methodology. It maps the origins of Participatory Action Research (PAR) and discusses the benefits and challenges that have been identified by other researchers in utilizing PAR approaches in conducting research.